THE IMPACT OF THE COMMUNITY ACQUIS ON FINANCIAL CONTROL IN ROMANIA - MIHAELA IULIANA DUMITRU (Annals of the University of Petrosani: Economics, 2014)
When we refer to financial control, we talk, in fact, about the possibility to analyse a set of objectives and guide marks established by entities in order prevent, correct, and subsequently eliminate irregularities, errors, deviations, etc. The main objective is to highlight them in the future with the purpose of obtaining maximum performance with minimum effort. This activity was deemed representative as object of a separate chapter within the community acquis (we are talking about chapter 28 “Financial control”. The problems concern specialised bodies, the control procedure, the reports resulted following the control, and their legal and economic effects.